Inner-self in the teaching of physical sciences according to the Curriculum and Assessment Policy Statement (CAPS) in South African schools. Issue 1 (2nd January 2023) - Mpungose, Cedric Bheki
ABSTRACT: Teachers of Physical Sciences (PS) according to the Curriculum Assessment Policy Statement (CAPS) are blamed for the high failure rate of learners resulting from inadequate subject content and pedagogy. However, little research has been done to look at the inner-self (self-identity) of those who teach. A qualitative interpretive case study was carried out on eight teachers of PS in rural schools in the province of KwaZulu-Natal in South Africa, to explore teachers' experiences and bring awareness of role of the inner-self in the teaching of CAPS PS. Reflective activities, document analysis and one-on-one semi-structured interviews were used to generate data, which were thematically analysed and framed by deep curriculum. Teachers focus a great deal on the outer-self (content and pedagogy), while lacking insight into the inner-self, and this leads them to lose self-direction/confidence in the teaching process. Failure to teach from within results in poor performance in a subject. This study recommends the inner-outer-self framework as a useful tool that can assist and bring awareness to PS teachers, to encourage them to teach from the inner-self within to the outer-self, in order to improve their performance, particularly among those teaching PS in rural schools.